1975
DOI: 10.1038/bjc.1975.136
|View full text |Cite
|
Sign up to set email alerts
|

The metastatic patterns of osteosarcoma

Abstract: Summary.-The paper presents a detailed comparison of the anatomical distribution and frequency of clinically evident metastases in 152 cases of osteosarcoma, and autopsy findings in 43 cases. The behaviour of long bone tumours is contrasted with those arising elsewhere, which tend to metastasize less widely because of early death from effects of the primary tumour. In both clinical and autopsy series long bone tumours produced lung metastases (LM) in over 90% of patients dying with metastases, but the terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
138
1
3

Year Published

1977
1977
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(143 citation statements)
references
References 3 publications
(1 reference statement)
1
138
1
3
Order By: Relevance
“…Korn reich et al 42 reported on a patient who was found to have osteoblastic osteosarcoma of the distal femur and a calvarial metastasis. 26,36,42 The tumor invaded the dura and could not be separated from it. 42 The metastatic tu- mor in our series also demonstrated extensive dural invasion, whereas both primary tumors did not.…”
Section: Previously Reported Pediatric Cases Of Cranial Osteosarcomamentioning
confidence: 99%
“…Korn reich et al 42 reported on a patient who was found to have osteoblastic osteosarcoma of the distal femur and a calvarial metastasis. 26,36,42 The tumor invaded the dura and could not be separated from it. 42 The metastatic tu- mor in our series also demonstrated extensive dural invasion, whereas both primary tumors did not.…”
Section: Previously Reported Pediatric Cases Of Cranial Osteosarcomamentioning
confidence: 99%
“…Moreover, Dahlin 8z Coventry (1967) and Jaffe (1958) found a better 5-year survival after tumours affecting the tibia than the femur. Jeffree et al (1975) found relatively few extrapulmonary metastases from tumours in the tibia. Others (Stanley 8z MacKenzie 1964, Scranton et al 1975 could not confirm this finding.…”
Section: Discussionmentioning
confidence: 97%
“…En sık uzak metastaz görülen organ akciğerlerdir. Osteosarkom metastazlarının yaklaşık %80'i akciğer metastazlarıdır (14)(15)(16). Bu yazıda bahsedilen www.respircase.com olguda tutulan bölge proksimal humerustu ve tanı esnasında takibe alınması planlanan kalsifiye plevral plakların, kontrol tomografilerde progrese olmalarıyla metastaz oldukları anlaşıldı.…”
Section: Discussionunclassified